(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2022)
The article analyzes the concepts of "inclusive competence", "volunteer", "volunteering","volunteering", "volunteer movement", "volunteering" and formulates the definition of "inclusivecompetence of future volunteer teachers". We understand the inclusive competence of future volunteerteachers as a complex system of future teachers' abilities to volunteer in an inclusive educationalenvironment, which is manifested in their values of inclusive education and involves emotional,empathetic, socionic, communicative skills in working with people with special needs. educational needs.The structure and components and indicators of inclusive competence are studied, the relationshipbetween the formation of inclusive competence, preparation of future teachers for volunteering and thecomponent composition of the readiness of future volunteer teachers to work in an inclusive educational environment is emphasized. It is determined that the readiness of future teachers to volunteer in aninclusive educational environment will mean the inclusive competence of volunteer teachers, whichincludes: value-motivational, content-procedural, emotional-volitional, reflective components. We believethat inclusive competence is a component of professional competence and is inextricably linked with theprocess of implementing personally and socially important activities. It was emphasized that the inclusionof inclusive competence and the introduction of volunteering in educational activities will promote theprofessional development of future teachers. Barriers to the spread of volunteering in educationalinstitutions have been identified and ways to overcome them in an inclusive educational environment byfuture volunteer teachers have been suggested.